Cross-border bank flows and monetary policy: Implications for Canada - Ricardo Correa; Teodora Paligorova; Horacio Sapriza; Andrei Zlate (Bank of Canada, 2017)
Using the Bank for International Settlements (BIS) Locational Banking Statistics data on bilateral bank claims from 1995 to 2014, we analyze the impact of monetary policy on cross-border bank flows. We find that monetary policy in a source country is an important determinant of cross-border bank flows. In addition, we find evidence in favor of a cross-border portfolio channel that works in parallel with the traditional bank lending channel. As tighter monetary conditions in source countries erode the net worth and collateral values of domestic borrowers, banks reallocate credit away from relatively risky domestic borrowers toward safer foreign counterparties. The cross-border reallocation of credit is more pronounced for source countries with weaker financial sectors that are likely more risk averse. Also, the reallocation is directed toward borrowers in advanced economies, or those in economies with investment-grade sovereign rating. In particular, source countries with tighter monetary policy increase cross-border credit to Canada. Our study highlights the spillovers of domestic monetary policy on foreign credit, which enhances the understanding of the international monetary transmission mechanism through global banks.
Keywords: F34; F36; G01; 330; Financial institutions; Monetary policy